2008
DOI: 10.1061/(asce)0887-3828(2008)22:6(398)
|View full text |Cite
|
Sign up to set email alerts
|

Shanghai’s Experience on Utilizing the Rubblization for Jointed Concrete Pavement Rehabilitation

Abstract: As agencies continue looking for cost-effective methods to rehabilitate deteriorated JCP, rubblization using resonant breaker has been experimented by the Shanghai Municipal Roadway Authority (SMRA). It was demonstrated that rubblization using resonant breaker offers a viable option for the SMRA because the rubblized pavement sections have been performing very well with no visible distress. Based on field observation for a typical HMAC overlay on a non-rubblized JCP, it was found the treatment normally would h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…92 Various restoring treatments have been applied to these deteriorated pavements in an effort to 93 extend the service lives of the pavements. However, field surveys and observations indicated 94 that even with a costly rehabilitation program such as full depth repairing and undersealing 95 voids with grout, these maintained PCC pavements still could not keep a satisfactory 96 condition and continued to deteriorate noticeably (Chen et al 2008). A more cost-effective 97 rehabilitation strategy for the deteriorated PCC pavements would be needed.…”
mentioning
confidence: 91%
“…92 Various restoring treatments have been applied to these deteriorated pavements in an effort to 93 extend the service lives of the pavements. However, field surveys and observations indicated 94 that even with a costly rehabilitation program such as full depth repairing and undersealing 95 voids with grout, these maintained PCC pavements still could not keep a satisfactory 96 condition and continued to deteriorate noticeably (Chen et al 2008). A more cost-effective 97 rehabilitation strategy for the deteriorated PCC pavements would be needed.…”
mentioning
confidence: 91%
“…Among the old concrete-pavement-crushing and reconstruction methods, homogenized micro-crack crushing is a novel concrete-pavement-crushing technology. This method combines the advantages of multiple head breakers, impact compactors, guillotine breakers, and resonant pavement breakers, which makes full use of the bearing capacity of the original pavement and treats the corresponding problems [3][4][5][6][7][8]. When old concrete pavement is rehabilitated by homogenized micro-crack crushing technology, special mechanical equipment is used to crush the old concrete pavement.…”
Section: Introductionmentioning
confidence: 99%
“…Rubblization is an in-place rehabilitation technique that involves breaking the concrete pavement into pieces. The sizes of the broken pieces usually range from sand size to 75 mm (3 in) at the surface and 305 to 381 mm (12 to 15 in) on the bottom part of the rubblized layer (Von Quintus et al 2007) Considerable research in US and east Asia (PCS/Law 1991;NAPA 1994;Thompson et al 1997;Ksaibati et al 1998;Heckel 2002;Baladi et al 2002;Timm and Warren 2004;Gulen et al 2004;Scullion 2006;Wienrank and Lippert 2006;Von Quintus et al 2007;Chen et al 2008;Gucunski et al 2009) has been conducted on rubblization in the recent past but this technique were not much studied in European countries as considering several research efforts for other fracture technique such as cracking and seat (Ellis et al 2002). The results of research in US indicated that the performance of this technique varied from place to place and from project to project.…”
Section: Introductionmentioning
confidence: 99%